2017
DOI: 10.2196/jmir.6302
|View full text |Cite|
|
Sign up to set email alerts
|

“You Sort of Go Down a Rabbit Hole...You’re Just Going to Keep on Searching”: A Qualitative Study of Searching Online for Pregnancy-Related Information During Pregnancy

Abstract: BackgroundThe Web is becoming increasingly popular for gaining information on medical or health issues; with women in particular likely to search online for this type of information and support. Despite the increased use of the Web for health-related information, we need to question whether the Web and the ease of seeking health information that it provides leads to more (patient) empowerment. As well as being a time of joy and expectations, pregnancy can be a worrying time for women, especially first time mum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
1
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 15 publications
(38 reference statements)
5
76
1
11
Order By: Relevance
“…One US study found Google searches were the most common mode of information seeking, particularly early in pregnancy [16]. An important factor for many women was the ability to obtain information instantly and easily [6,15,17,18]. Importantly, in one global study almost half of the 613 women surveyed reported that their online information-seeking was triggered by dissatisfaction with health professionals regarding both the information provided and insufficient time to ask questions.…”
Section: The General Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…One US study found Google searches were the most common mode of information seeking, particularly early in pregnancy [16]. An important factor for many women was the ability to obtain information instantly and easily [6,15,17,18]. Importantly, in one global study almost half of the 613 women surveyed reported that their online information-seeking was triggered by dissatisfaction with health professionals regarding both the information provided and insufficient time to ask questions.…”
Section: The General Populationmentioning
confidence: 99%
“…Facebook, discussion forums) features frequently in research on pregnancy information seeking and can be an important way for women to find support, develop networks, and foster emotional well-being [22,23]. Social media platforms, which are usually accessed via an app on women's phones, also provide women with an setting in which they can acquire and share (nonmedical) knowledge and expertise about motherhood [24], and are a helpful way for women to get an idea of whether their symptoms and experiences in pregnancy are "normal" [17,25]. Apps with social media functionality may be particularly useful in late pregnancy and the postnatal period when needs change from seeking information to seeking support (community), and avoiding isolation [22].…”
Section: The General Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found that peer-to-peer online platforms can be sources of information and support. Peers provide these sources themselves by helping other users or to emotionally support each other [7][8][9][10][11][12]. Online empowering processes can facilitate empowering outcomes outside the online environment such as being better informed, feeling more confident with the physician, and improved acceptance of the disease [1].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers are using SNSs such as Facebook increasingly for recruitment to health related studies [4,5]. In addition, there has been an increase in the use of SNSs such as Facebook, Twitter, and YouTube for health related information seeking and sharing [6][7][8][9][10][11], for health related topics such as diabetes [12,13], pregnancy [14], and asthma [15].…”
Section: Introductionmentioning
confidence: 99%